Retrospective analysis (2009–2017) of factors associated with progression and regression of non-alcoholic fatty liver disease (Hepatic steatosis) in patients with type 2 diabetes seen at a tertiary diabetes centre in Southern India. Issue 5 (September 2021) - Kamalraj, Nithyanantham; Sathishkumar, Madhanagopal; Arunvignesh, Mani; Baskar, Viswanathan; Jebarani, Saravanan; Amutha, Anandakumar; Deepa, Mohan; Shanthi Rani, Coimbatore Subramanyam; Chandru, Sundaramoorthy; Unnikrishnan, Ranjit; Anjana, Ranjit Mohan; Harish, Mardavada; et al.
Abstract: Aim: To identify the profiles and factors associated with progression/regression of ultrasound-derived hepatic steatosis with type 2 diabetes mellitus seen at a tertiary diabetes center in southern India. Methods: Participants were individuals with type 2 diabetes mellitus with at least two consecutive ultrasound measurements available. Hepatic steatosis was assessed using high-resolution B-mode ultrasonography. Admittedly ultrasonography has lower sensitivity and specificity, however, it is the only modality available in a routine clinical setting to screen for hepatic steatosis. Progression or regression of hepatic steatosis was assessed after a mean follow-up of 3.0 ± 2.1 years and correlated with clinical and biochemical parameters. Results: A total of 1835 participants with type 2 diabetes mellitus were studied, of whom 88.6% had some form of hepatic steatosis at baseline which included mild steatosis (grade 1) in 982 (53.5%), moderate steatosis (grade 2) in 628 (34.2%) and severe steatosis (grade 3) in 15 (0.8%). Hepatic steatosis progression, regression or no change in grade of hepatic steatosis were seen in 21.5%, 26.6% and 51.9% of participants. Increase in body weight, body mass index, glycated haemoglobin, serum triglycerides and gamma glutamyl transferase were the factors associated with progression of hepatic steatosis, whereas regression showed reduction in body weight, body mass index, fasting plasma glucose and glycated haemoglobin. Conclusion: Among South Indian type 2 diabetes patients with hepatic steatosis, severity of steatosis progressed in 1/3rd while it regressed in 1/4th. These retrospective data need proper ascertainment in controlled studies. Highlights: In Asian Indians with T2D and ultrasound-derived hepatic steatosis, one third progressed with respect to its severity. A fourth of individuals with T2D and hepatic steatosis, regressed with respect to severity of hepatic steatosis. Obesity, hypertriglyceridemia and glycated hemoglobin are the key risk factors for hepatic steatosis. Weight reduction, wherever appropriate, aids in preventing progression and promoting regression of hepatic steatosis.